STAGED TREATMENT OF CHILDREN WITH POSTTRAUMATIC TRACHEOESOPHAGEAL FISTULA - V. N. Stalmakhovich; I. N. Kaygorodova; E. V. Sapukhin; I. B. Li; A. P. Dmitrienko; L. V. Angarkhaeva (Acta Biomedica Scientifica, 2017)
The article presents the analysis of treatment of posttraumatic tracheoesophageal fistula caused by long staying of a flat battery in the esophagus lumen. The analysis cover treatment of two children at the age of 8 months and 1 year 3 months with a severe chemical burn of the esophagus because of long staying of a flat battery in the esophagus lumen. A principal clinical symptom of a disease was a dysphagia. The call for medical help was delayed - from 1 to 3 days. During the first esophagoscopy the excision of battery was done. A total necrosis of a front and lateral side of the esophagus in a cervical esophagus and a backside of trachea caused by the growth of atracheoesophageal fistula. A gastric fistula was performed for food supply. An emerged tracheoesophageal fistula led to the disturbance of breathing, which is why tracheostomy was urgently performed. The first child had a one-stage plastic operation of backside of trachea defect, the second child had a cycling off fragment of the esophagus, this had made it possible to pack off the trachea and stabilize the children's condition. In three months, the children had undergone a reconstructive plastic operation - retrosternal coloesophagoplasty with an extirpation of an esophagus stump. In this case, a backside of trachea was formed from the diverticulum of trachea (a segment of the esophagus after its disconnection).